PENGARUH RENANG INTENSITAS RENDAH (LOW INTENSITY SWIMMING) TERHADAP KAPASITAS VITAL PARU - Maharani, Purindri; Suharno, Suharno; Kusuma, MNH (Jurusan Kedokteran FK Unsoed, 2014)
Pulmonary disease was ranked on the third place of the most common disease with the prevalence of 17%. Pulmonary disease can lead to a decrease in vital capacity of the lungs. Vital capacity of the lungs are also affected by other factors such as body mass index, gender, age, as well as physical activity. Several previous studies have shown that swimming activity can increase lung capacity and the ability of respiration as well. Based on these results, the aim of this study was to determine the effect of swimming on lung vital capacity changes at male medical students.This study using pre-experimental with pre and post test design and twenty male of medical students (mean age 19.5±1.5 yr;bmi 21.9±3.4kg/m²) were selected by consecutive sampling technique and adjusted to inclusion and exclusion criteria. Spirometry inspection, chest radiographs through X-ray and ECG was also done interpreted by medical specialists to ensure that the samples did not have a history of cardiac as well as pulmonary disease.Swimming was conducted for 2 weeks with a frequency of 1 time a week for 30 minutes. The method of training using repetition interval extensive by dividing the volume of exercises into 5 series. Each series of exercises performed for 6 minutes easy swimming in training zone of 70%-85% of MEHR (Maximum Exercises Heart Rate) with rest periods between series for 15 minutes. Measurements of lung vital capacity was done twice, ie prior and post of intervention and the data would be statistically analyzed by paired t-test method. The result showed that there is a significant difference of lung vital capacity pre and post intervention. The means of lung vital capacity pre and post was increased by 3.6 ± 0.5 liters to 3.9 ± 0.6 liters, test paired t-test indicates a mean value of 3.7 ± 0.3 liters (p = 0.000, p <0.05), by the confidence intervals of 95%. This value indicates that there is positive effect of swimming activity to changes in lung vital capacity of males medical students of Jenderal Soedirman University.